A STUDY ON THE EFFECT OF ADDITIONAL BACKWARD WALKING TRAINING ON BALANCE AND FUNCTIONAL OUTCOMES IN PATIENTS WITH STROKE - KALYANA, SHUBHAM; LOHAR, DEEPAK; KHAN, JAFAR; RAO, LAKSHITA SINGH (International Journal of Current Pharmaceutical Research, 2023)
Objective: Stroke is a significant cause of mortality and disability globally, with a higher prevalence in urban areas of India compared to rural regions. Men in India face a greater risk of stroke, attributed to factors such as smoking and drinking, which are more prevalent among Indian men. This study aimed to evaluate the influence of backward walking training on balance and functional outcomes in stroke patients. Methods: Experimental Group received 30 min of backward walking training three times per week for three weeks. Balance was assessed using the Berg Balance Scale (BBS), and functional outcomes were measured using the Barthel Index (BI) before and after the intervention. Data analysis was performed using Student's paired t-test and unpaired t-test. Results: Before the intervention, there were no significant differences between the Control Group and Experimental Group in terms of BBS and BI scores. However, after the intervention, the Experimental Group showed a significant improvement in both balance (BBS) and functional outcomes (BI) compared to the Control Group. The Experimental Group demonstrated a greater improvement in BI scores (9.94%) compared to the Control Group (4.95%), and a similar pattern was observed for BBS scores, with the Experimental Group showing a greater improvement (7.87%) compared to the Control Group (3.49%). These differences were statistically significant (p<0.01), indicating that the intervention in the Experimental Group was more effective than the Control Group. Conclusion: These findings suggest that incorporating backward walking training into stroke rehabilitation programs can be beneficial for patients in terms of enhancing their balance and functional abilities.